Nowy ład w Europie Środkowej w myśli politycznej Narodowo-Ludowej Organizacji Wojskowej w czasie drugiej wojny światowej - Miszewski, Dariusz (Saeculum Christianum. Pismo Historyczne, 2019)
The NLOW (National People's Military Organisation, NPMO) did not accept the idea of a federation (the Polish-Czechoslovak union, Jagiellonian idea, idea of Intermarium). The basis of its concept of Poland's security was the national state with strategic boundaries: in the west (the Oder – the Lusatian Neisse), north (from the Oder to Courland), east (Dmowski’s line). Neighbours adjacent to it would enter the Polish security area. Belarusian and Ukrainian minorities would be subject to gradual assimilation. Lithuania would have national and cultural autonomy within Poland. Germans and Jews would be banished from it. In order to stop the imperialism of Germany and the USSR, Poland would organize a block of Slav national states (the West Slavonic State). It would be responsible for foreign and military policy. It would also include a close alliance with Catholic national states (Latin block).